HIV drug resistance among adults initiating antiretroviral therapy in Uganda - Watera, Christine; Ssemwanga, Deogratius; Namayanja, Grace; Asio, Juliet; Lutalo, Tom; Namale, Alice; Sanyu, Grace; Ssewanyana, Isaac; Gonzalez-Salazar, Jesus Fidel; Nazziwa, Jamirah; Nanyonjo, Maria; Raizes, Elliot; et al. (Journal of Antimicrobial Chemotherapy, 2021)
WHO revised their HIV drug resistance (HIVDR) monitoring strategy in 2014, enabling countries to generate nationally representative HIVDR prevalence estimates from surveys conducted using this methodology. In 2016, we adopted this strategy in Uganda and conducted an HIVDR survey among adults initiating or reinitiating ART. Methods: A cross-sectional survey of adults aged 18 years initiating or reinitiating ART was conducted at 23 sites using a two-stage cluster design sampling method. Participants provided written informed consent prior to enrolment. Whole blood collected in EDTA vacutainer tubes was used for preparation of dried blood spot (DBS) specimens or plasma. Samples were shipped from the sites to the Central Public Health Laboratory (CPHL) for temporary storage before transfer to the Uganda Virus Research Institute (UVRI) for genotyping. Prevalence of HIVDR among adults initiating or reinitiating ART was determined.
Keywords: HIV; Drug; Adults; Antiretroviral therapy; Uganda